Marketing strategies for Singapore consulting firms - Xie, Tong. (2008)
Investigate how marketing strategy is important to consulting firms in the Singapore construction industry, with a focus on areas such as competitive strategy practices in organizations, competitive strategy formulation, competitive implementation and competitive evaluation.